Preface - Borkowski, Adam (Computer Assisted Methods in Engineering and Science, 2011)
The present issue of CAMES reflects the outcome of the 19th International Conference on Computer Methods in Mechanics (CMM 2011). This meeting was held on May 9–12, 2011, at the Warsaw University of Technology and gathered over 250 participants from 27 countries. The CMM 2011 had a rich scientific program encompassing 6 plenary lectures, 31 keynote lectures given within 15 minisymposia, eight thematic sessions and five ordinary sessions. The scope of the conference covered broad spectrum of issues in computational mechanics, including numerical modeling of materials and structures, mesh-based and mesh-less methods of analysis, inverse problems and optimisation, bio- and fluid-mechanics, heat transfer, multiscale modeling and nano-mechanics.